2001
DOI: 10.1086/320188
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low‐Dose Intermittent Subcutaneous Interleukin (IL)–2 in Antiviral Drug–Experienced Human Immunodeficiency Virus–Infected Persons with Detectable Virus Load: A Controlled Study of 3 IL‐2 Regimens with Antiviral Drug Therapy

Abstract: To evaluate the safety and efficacy of 3 regimens of intermittent subcutaneous (sc) interleukin (IL)--2 in a phase 2 study, 61 antiviral drug-experienced human immunodeficiency virus (HIV)--positive patients were randomly assigned to one of the following study arms: antiretroviral therapy (ART) plus IL-2 (12 million IU [MIU] by continuous intravenous infusion, followed by 7.5 MIU twice a day, sc, every 8 weeks); ART plus IL-2 (7.5 MIU twice a day, sc, every 8 weeks); ART plus IL-2 (3 MIU twice a day, sc, every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…However, if the primary role of IL-2 is to promote tolerance, the outcome of these trials may to some degree reflect the consequence of manipulating the Treg compartment. IL-2 therapy resulted in a sustained increase in CD4 T-cell counts for most patients (19,70,125), and the effect appeared to be long lasting as shown by 10-year follow-up studies (75). In a pooled retrospective analysis of IL-2 given intravenously, plasma HIV RNA levels were significantly lower in IL-2-treated patients than in patients receiving antiretroviral therapy only (32).…”
Section: Foxp3 In Human Cells Similar To Results With Scurfy and Foxp3mentioning
confidence: 99%
“…However, if the primary role of IL-2 is to promote tolerance, the outcome of these trials may to some degree reflect the consequence of manipulating the Treg compartment. IL-2 therapy resulted in a sustained increase in CD4 T-cell counts for most patients (19,70,125), and the effect appeared to be long lasting as shown by 10-year follow-up studies (75). In a pooled retrospective analysis of IL-2 given intravenously, plasma HIV RNA levels were significantly lower in IL-2-treated patients than in patients receiving antiretroviral therapy only (32).…”
Section: Foxp3 In Human Cells Similar To Results With Scurfy and Foxp3mentioning
confidence: 99%
“…IL-2, a ␥c-cytokine activating STAT5, 4 is currently in a phase III efficacy trial as a potentially effective therapy in HIV disease based on its capacity to expand CD4 ϩ T lymphocytes without increasing viral load. [71][72][73][74] When we compared the impact of intermittent IL-2 administration on STAT5 activation in individuals who responded either well or poorly in terms of CD4 ϩ T cell count increase, we observed that STAT5⌬ activation was more prominent in the good versus the poor responder. 6 Like IL-2, GM-CSF is also currently being studied for its hematopoietic reconstitution capacity and as a potential adjuvant to antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several cytokines, including IL-2, IL-7, and IL-15, which share a common γ chain, might have putative roles in improving control of HIV-1 infection; of these, IL-2 is the best characterized (2)(3)(4). Although recombinant human IL-2 (rhIL-2) plus HAART produced significant CD4 + T lymphocyte expansion without an increase in viral load (5)(6)(7)(8), the effects of this combination on purging viral reservoirs is somewhat unclear (2,3).…”
Section: Introductionmentioning
confidence: 99%